2008
DOI: 10.1073/pnas.0706335105
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of extracellular microfibrils: Multimerization of the fibrillin-1 C terminus into bead-like structures enables self-assembly

Abstract: Microfibrils are essential elements in elastic and nonelastic tissues contributing to homeostasis and growth factor regulation. Fibrillins form the core of these multicomponent assemblies. Various human genetic disorders, the fibrillinopathies, arise from mutations in fibrillins and are frequently associated with aberrant microfibril assembly. These disorders include Marfan syndrome, Weill-Marchesani syndrome, Beals syndrome, and others. Although homotypic and heterotypic fibrillin self-interactions are consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(122 citation statements)
references
References 34 publications
6
116
0
Order By: Relevance
“…Heparin did not inhibit this interaction in concentrations up to 200 g/ml (ϳ13 M), indicating different binding epitopes (data not shown). Recently, we demonstrated that C-terminal fibrillin-1 fragments have the propensity to multimerize into structures with similarity to the beads found in the bead-on-a-string-structured, extracted microfibrils (Hubmacher et al, 2008). It was further shown that this multimerization significantly increases the avidity for the self-interaction of the fibrillin-1 C-terminus with the N-terminus.…”
Section: Fibrillins and Fibronectin Interact Directlymentioning
confidence: 97%
See 4 more Smart Citations
“…Heparin did not inhibit this interaction in concentrations up to 200 g/ml (ϳ13 M), indicating different binding epitopes (data not shown). Recently, we demonstrated that C-terminal fibrillin-1 fragments have the propensity to multimerize into structures with similarity to the beads found in the bead-on-a-string-structured, extracted microfibrils (Hubmacher et al, 2008). It was further shown that this multimerization significantly increases the avidity for the self-interaction of the fibrillin-1 C-terminus with the N-terminus.…”
Section: Fibrillins and Fibronectin Interact Directlymentioning
confidence: 97%
“…The multimerization of the fibrillin-2 (rFBN2-C) and fibrillin-3 (rFBN3-C) recombinant C-terminal halves were analyzed by Superose 6 gel filtration chromatography (100-ml column on a high-precision Ä ktaPurifier 10; GE Healthcare) as described in detail for the fibrillin-1 C-terminal construct rFBN1-C (Hubmacher et al, 2008). Recombinant protein, 2.7 mg, previously purified by metal-chelating chromatography were loaded onto the column equilibrated with TBS, including 2 mM CaCl 2 at a flow rate of 0.5 ml/min.…”
Section: Size-exclusion Chromatography and Analysis Of The Fibrillin mentioning
confidence: 99%
See 3 more Smart Citations